Innovation in der Translation. Aspekte der Patentübersetzung am Beispiel der Relation Deutsch-Polnisch - Łukasz M. Plęs (Linguistische Treffen in Wrocław)
The aim of the article is to present various aspects of the translation of patent documents from German into Polish. The translation of patents is a multidimensional issue, especially as translations of patent documents into Polish are required for patent validation in Poland. Patent documents represent a hybrid complex of technical content in a legal function. On the one hand, patent documents are characterised by a precise and comprehensible description, on the other hand, they must be written in such a diffuse manner that competitors are not able to derive their own development directly from them. Patent documents are deeply specialised in terms of content. Their typical characteristics include a variety of stylistic conventions and terminological peculiarities. For this reason, patent documents are a challenge for translators in many respects, especially as inconsistency with patent conventions can have serious consequences, i.e. affect the scope of protection. The article deals with aspects of patent translation, such as formal issues, text specifics, style, terminology, and the use of computer-assisted and machine translation.